2019
DOI: 10.1098/rspb.2019.2230
|View full text |Cite
|
Sign up to set email alerts
|

Deer movement and resource selection during Hurricane Irma: implications for extreme climatic events and wildlife

Abstract: Extreme climatic events (ECEs) are increasing in frequency and intensity and this necessitates understanding their influence on organisms. Animal behaviour may mitigate the effects of ECEs, but field studies are rare because ECEs are infrequent and unpredictable. Hurricane Irma made landfall in southwestern Florida where we were monitoring white-tailed deer ( Odocoileus virginianus seminolus ) with GPS collars. We report on an opportunistic case study of behavioural responses exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 90 publications
1
19
0
Order By: Relevance
“…These animals made use of spatial and temporal heterogeneity in temperatures in ways that may allow them to maintain their function as herbivores as temperatures increase. Thus, our results corroborate recent literature that argues for the incorporation of animal behavior into climate change studies (Abernathy et al, ; Buchholz et al, ; Harmon & Barton, ; Wong & Candolin, ). Further, our results demonstrate that managing habitats to provide thermal heterogeneity may allow wildlife to alter their behavior in ways that may ameliorate the effects of climate change.…”
Section: Resultssupporting
confidence: 91%
“…These animals made use of spatial and temporal heterogeneity in temperatures in ways that may allow them to maintain their function as herbivores as temperatures increase. Thus, our results corroborate recent literature that argues for the incorporation of animal behavior into climate change studies (Abernathy et al, ; Buchholz et al, ; Harmon & Barton, ; Wong & Candolin, ). Further, our results demonstrate that managing habitats to provide thermal heterogeneity may allow wildlife to alter their behavior in ways that may ameliorate the effects of climate change.…”
Section: Resultssupporting
confidence: 91%
“…Recent studies have suggested that behavioural plasticity may enable terrestrial mammal species to cope with unsuitable environmental conditions, allowing them to maintain their functional role in the ecosystems as climate changes (Abernathy et al, 2019;Buchholz et al, 2019;Wolff et al, 2020). In this study, both warmwater and cold-water affinity species showed the capacity to adjust their behaviour in space and time to cope with the seasonal thermal heterogeneity of the ecosystem.…”
Section: Niche Overlap and Climate Change Implicationsmentioning
confidence: 77%
“…Such responses will benefit individual survival if they reduce physiological stress or remove the threat, for example by moving away or entering torpor (e.g. at signs of extreme weather or an approaching fire: Nowack et al 2017 ; Abernathy et al 2019 ; Nimmo et al 2019 ) or altering behaviours (e.g. in response to a predator: Laundré et al 2001 ).…”
Section: Introductionmentioning
confidence: 99%